Circular RNA circPHKA2 Relieves OGD-Induced Human Brain Microvascular Endothelial Cell Injuries through Competitively Binding miR-574-5p to Modulate SOD2 - Xiaobo Yang (Hindawi Limited, 2021)
Background. Circular RNA phosphorylase kinase regulatory subunit alpha 2 (circPHKA2; hsa_circ_0090002) has a significantly, specifically different expression in acute ischemic stroke (AIS) patients’ blood. Here, we intended to investigate the role and mechanism of circPHKA2 in oxygen-glucose deprivation- (OGD-) induced stoke model in human brain microvascular endothelial cells (HBMEC). Methods. Expression of circPHKA2, microRNA- (miR-) 574-5p, and superoxide dismutase-2 (SOD2) was detected by quantitative PCR and western blotting. Cell injury was measured by detecting cell proliferation (EdU assay and CCK-8 assay), migration (transwell assay), neovascularization (tube formation assay), apoptosis (flow cytometry and western blotting), endoplasmic reticulum stress (western blotting), and oxidative stress (assay kits). Direct intermolecular interaction was determined by bioinformatics algorithms, dual-luciferase reporter assay, biotin-labelled miRNA capture, and argonaute 2 RNA immunoprecipitation. Results. circPHKA2 was downregulated in AIS patients’ blood in SOD2-correlated manner. Reexpressing circPHKA2 rescued EdU incorporation, cell viability and migration, tube formation, B cell lymphoma-2 (Bcl-2) expression, and SOD activity of OGD-induced HBMEC and alleviate apoptotic rate and levels of Bcl-2-associated protein (Bax), glucose-regulated protein 78 kD (GRP78), C/EBP-homologous protein (CHOP), caspase-12, reactive oxygen species (ROS), and malondialdehyde (MDA). Additionally, blocking SOD2 partially attenuated these roles of circPHKA2 overexpression. Molecularly, circPHKA2 upregulated SOD2 expression via interacting with miR-574-5p, and miR-574-5p could target SOD2. Similarly, allied to neurovascular protection of circPHKA2 was the downregulation of miR-574-5p. Conclusion. circPHKA2 could protect HBMEC against OGD-induced cerebral stroke model via the miR-574-5p/SOD2 axis, suggesting circPHKA2 as a novel and promising candidate in ischemic brain injury.